The Project-Based Learning Assessment Guide (Project-Based Learning) is oriented towards Phenomenon-Based Learning - Luh Nyoman Gita Acyuta Dewi; I Wayan Widiana; I Nyoman Laba Jayanta (Journal of Education Reseach and Evaluation, 2024)
Less than optimal use of learning assessments results in low students' computational thinking abilities. This research aims to develop a project-based learning assessment guide oriented to phenomenon-based learning for fourth-grade elementary school students in the Mathematics subject and to analyze the validity, practicality, and effectiveness of the project-based learning assessment guide oriented to phenomenon-based learning. This research is classified as development research using the ADDIE model. The subjects involved in this research included 4 learning assessment experts, 3 teacher practitioners, and 29 grade IV students. This research uses data collection techniques, namely questionnaires and tests. Data analysis techniques include descriptive, qualitative, quantitative, and inferential statistics. The results of this research are the results of validation by a learning assessment expert who obtained very good qualifications, the results of the practicality test by the teacher who obtained very good qualifications, and the results of the effectiveness test of the project-based learning assessment guide oriented to phenomenon-based learning, which showed that there was a significant difference in the computational thinking abilities of class IV students. In mathematics subjects before and after taking part in the lesson. Based on this research, the project-based learning assessment guide, which is oriented towards phenomenon-based learning, is effective because this learning assessment guide can help teachers carry out learning assessments. This research aims to improve the computational thinking skills of fourth-grade elementary school students in mathematics subjects.